Enhanced hydrogen production of acidified ruddlesden–popper type perovskite oxides in water and seawater by coupled piezo-photocatalysis. (March 2023) - Ma, X.; Gao, Y.; Yang, B.; Lou, X.; Huang, J.; Ma, L.; Jing, D.
Abstract: Photocatalytic water splitting for hydrogen production is more sustainable than traditional desalination and electrocatalysis because of avoiding electrode corrosion and other problems. Two-dimensional perovskite oxide materials have multiple characteristics, such as ferroelectric, piezoelectric, and pyroelectric properties, demonstrating good light response and chemical stability, which provides a broad prospect in photo-chemical conversion. In this study, acidified La2 NiO4 can greatly improve the amount of hydrogen evolution by coupling its piezocatalysis and photocatalysis. Under the full-spectrum illumination assisted with ultrasonic vibration in seawater, a recordable hydrogen production activity of 1315.44 μmol·g −1 ·h −1 was obtained in acidified La2 NiO4 by 0.006 mol/L HCl, which is more than 200 times higher than that of pure La2 NiO4 (6.89 μmol k·g −1 ·h −1 ) in methanol solution. It is found that the significant hydrogen production of La2 NiO4 samples treated with acidification lies in the fast separation of charge carriers in comparison with those without acidification. In addition, the hydrogen production efficiency of seawater is higher than that of pure water because the inorganic salt acts as a sacrificial agent and changes the surface charge of the catalyst. This work contributes to the in-depth understanding of piezo-photocatalysis and thus provides a new solution for improving the performance of multifield coupling hydrogen production. Graphical abstract: Image 1